Transformasi Human Resource Management dalam Koperasi: Strategi untuk Meningkatkan Kinerja dan Keterlibatan Anggota - Muhammad Ali; Muslikun Muslikun (PUTRA JAWA PUBLISHER, 2024)
In this paper, the authors discuss the transformation of human resource management (HRM) in cooperatives and the innovative strategies implemented to improve performance and member engagement. In the context of a rapidly changing business environment and the increasing need for operational efficiency, cooperatives face challenges in adapting conventional HRM practices. This article explores various modern approaches, including the utilization of digital technology, competency-based training, and improved internal communication, to create a more dynamic and productive work environment. Using case studies and empirical data, this article assesses the impact of Human Resource Management (HRM) transformation on the achievement of cooperative goals, and provides recommendations for the implementation of these strategies in local and global contexts.